Mechanism of Action of Camptothecin - Liu, L.F.; Shyamal D., Desai; Li, Tsai-Kun; Mao, Yong; Mei, Sun; Sim, S.P (Annals of the New York Academy of Sciences, 2006)
Camptothecin (CPT) class of compounds has been demonstrated to be effective against a broad spectrum of tumors. Their molecular target has been firmly established to be human DNA topoisomerase I (topo I). CPT inhibits topo I by blocking the rejoining step of the cleavage/religation reaction of topo-I, resulting in accumulation of a covalent reaction intermediate, the cleavable complex. The primary mechanism of cell killing by CPT is S-phase-specific killing through potentially lethal collisions between advancing replication forks and topo-I cleavable complexes. Collisions with the transcription machinery have also been shown to trigger the formation of long-lived covalent topo-I DNA complexes, which contribute to CPT cytotoxicity. Two novel repair responses to topo-I-mediated DNA damage involving covalent modifications of topo-I have been discovered. The first involves activation of the ubiquitin/26S proteasome pathway, leading to degradation of topo-I (CPT-induced topo-I downregulation). The second involves SUMO conjugation to topo-I. The potential roles of these new mechanisms for repair of topo-I-mediated DNA damage in determining CPT sensitivity/resistance in tumor cells are discussed.